Prevalence and characteristics of pruritus in patients treated with different dialysis modalities - Vuksanović, Saša; Adamov, Nina; Balo, Mario; Trbojević Stanković, Jasna (Medicinski podmladak, 2020)
Introduction: Uremic pruritus is a common symptom in patients with end-stage renal disease (ESRD). Intense pruritus can lead to uncontrollable scratching, impaired sleep, anxiety, depression, therefore significantly lowering patient’s life quality. Although the prevalence of uremic itch in patients on dialysis has declined over the time, it is still present in peritoneal dialysis (PD) and hemodialysis (HD) patients. Aim: The aim of this study is to investigate the prevalence of pruritus in HD patients compared to PD patients, as well as possible differences in its presentation and correlation with demographic and clinical characteristics of the population. Material and methods: A total of 50 HD and 50 PD patients were included. Dialysis modality, patient demographic, clinical characteristics, and laboratory data were recorded. Data on the presence and duration of itching, skin dryness and scaling were obtained from a general itch questionnaire. The visual-analogue scale (VAS) and the 5-D itch scale were used for evaluation of pruritus. Results: Pruritus was present in 42% of PD patients and 24% of HD patients (p=0,056), without statistically significant differences in the distribution and intensity of pruritus in patients on different dialysis modality. A significantly higher number of PD patients had dry (41 vs 31; p= 0.026) and scaling skin (31 vs 15; p = 0.001). PD patients with pruritus had significantly higher levels ​​of intact parathyroid hormone (iPTH) (386,57±302,29pg/mL vs 159,25±163,52pg/mL; p=0,033) and AST (23,84±11,36U/L vs 14,17±3,73U/L; p=0,002), while having significantly lower levels ​​of urea (18,78±7,60mmol/L vs 23,65±4,31mmol/L; p=0,028), creatinine (717,96±229,50μmol/L vs 940,06±207,57μmol/L; p=0,009) and potassium (4,17±0,63mmol/L vs 5,80±0,80mmol/L; p=0,000) in comparison to HD patients with pruritus. Conclusion: Pruritus is a common symptom among ESRD patients treated with dialysis. In our study, a higher prevalence of pruritus was observed in PD patients. Dry skin and higher levels of​​ iPTH have been singled out as possible contributing factors to the occurrence of itch. Keywords: hemodialysis, peritoneal dialysis, uremic pruritus